2017
DOI: 10.1161/jaha.116.005163
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐Blocker Use Is Associated With Impaired Left Atrial Function in Hypertension

Abstract: Background--Impaired left atrial (LA) mechanical function is present in hypertension and likely contributes to various complications, including atrial arrhythmias, stroke, and heart failure. Various antihypertensive drug classes exert differential effects on central hemodynamics and left ventricular function. However, little is known about their effects on LA function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
2
11
0
3
Order By: Relevance
“…A previous study demonstrated that beta blockers had no effect on the LA functions in patients with heart failure . Another study showed that beta blocker use was associated with a decreased LA function in hypertensive patients . The differences in the results of our studies can be explained by the facts that we excluded patients with hypertension and recruited patients who were about 3 decades younger.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A previous study demonstrated that beta blockers had no effect on the LA functions in patients with heart failure . Another study showed that beta blocker use was associated with a decreased LA function in hypertensive patients . The differences in the results of our studies can be explained by the facts that we excluded patients with hypertension and recruited patients who were about 3 decades younger.…”
Section: Discussionmentioning
confidence: 74%
“…34 Another study showed that beta blocker use was associated with a decreased LA function in hypertensive patients. 35 The differences in the results of our studies can be explained by the facts that we excluded patients with hypertension and recruited patients who were about 3 decades younger. Also, in contrast with the patients in that study, our patients used the lowest dose of beta blockers and did not take other drugs.…”
Section: Discussionmentioning
confidence: 84%
“…15 LA analyses were performed using cvi42 image analysis software (Circle Cardiovascular Imaging Inc., Calgary, Canada). LA endocardial borders were manually traced in apical 2- and 4-chamber views using LV end-diastole as the point of reference.…”
Section: Methodsmentioning
confidence: 99%
“…Возможно, подобное различие в проаритмических и прогностических эффектах атенолола и лозартана связано с неодинаковым влиянием препаратов на ремоделирование ЛП [66], о чем, кроме того, свидетельствуют опубликованные в этом году результаты исследования Sardana и соавт. [67], в котором было показано, что у пациентов с АГ прием ББ по сравнению с другими антигипертензивными препаратами ассоциировался с худшей функциональной сохранностью ЛП. Вместе с тем поперечный дизайн исследования не позволяет оценить причинно-следственный характер связи между используемым препаратом и ремоделированием ЛП.…”
Section: центральное давление и диастолическая дисфункция левого желуunclassified